Cover Picture: Macromol. React. Eng. 5/2014. Issue 5 (May 2014) - Brunotte, Rene; Nagel, Jürgen; Mennig, Günter; Heinrich, Gert; Gehde, Michael
<x xml:space="preserve">Abstract</x> Cover: The modification of polyolefin surfaces during injection molding reveals positive results, especially using liquid modifiers. By varying the injection parameters, such as mold temperature and injection speed, polyolefin parts possessing high surface energies and bondings with high shear strengths are generated. Further details can be found in the article by R. Brunotte, J. Nagel, * G. Mennig, G. Heinrich, M. Gehde on page 412. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>